Some Further Notes on the Traprain Law Treasure - Curle, Alexander O (Proceedings of the Society of Antiquaries of Scotland, 1931)
Note on the curious letter which appeared twice in the inscription surrounding the base of the neck of the small silver flask and discussion of parallels on two Roman memorial stones.